Novel CuO/Mn3O4/ZnO nanocomposite with superior photocatalytic activity for removal of Rabeprazole from water - Sauvik Raha (Nature Portfolio, 2021)
Abstract In this work, a nanohybrid of CuO/Mn3O4/ZnO was generated through a simple hydrothermal based procedure. The CuO/Mn3O4/ZnO nanohybrid has been characterized using X-ray diffraction, transmission electron microscopy high resolution transmission electron microscopy, X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray analysis. UV–visible spectrophotometry and photoluminescence techniques allowed evaluation of optical properties that additionally suggested the prevalence of strong interfacial interaction between the three moieties of the nanohybrid and suppressed electron–hole recombination. The hybrid photocatalyst brought on ~ 97.02 ± 1.15% disintegration of rabeprazole when illuminated with visible light. The progress of the photodegradation was in conformity with pseudo-first order kinetic model and had a velocity constant of 0.07773 min−1. Additionally, ~ 84.45% of total organic carbon removal was achieved while chemical oxygen demand was reduced by ~ 73.01%. Using high resolution liquid chromatograph mass spectrometry technique, identification of the degraded products was made and accordingly the mechanistic route of the aforesaid degradation was proposed.